Analysis of the Influence of Social Media Marketing and Price Discounts on Online Purchase Decisions with Brand Trust as an Intervening Variable in the Tik-Tokshop Application in Soloraya - Rachmat Ramadhan; Moechammad Nasir (LPPM STIE EKA PRASETYA, 2023)
B